TEACHER PROFESSIONALISM IN MODERATING THE INFLUENCE OF ETHNO-BASED AUGMENTED REALITY ON TPACK - Rusyida, Wilda Yulia; Sari, Nurul Husnah Mustika; Ulhak, Zaki Dia; Prayoga, Susilo Adi; Pratama, Veranda Ardiyan Putra (Universitas Labuhanbatu, 2025)
Purpose- This study aims to determine: (1) the effect of Augmented Reality (AR) on teachers' Technological Pedagogical and Content Knowledge (TPACK); and (2) whether teacher professionalism strengthens the effect of Augmented Reality on TPACK.Methodology- This research employed a quantitative approach using moderated regression analysis (MRA) as the data analysis technique. Data were collected through questionnaires measuring teachers' ability to use ethnomathematics-based Augmented Reality and their TPACK levels.Findings-The results showed that ethnomathematics-based augmented Reality significantly influenced teachers' TPACK, with a significance value of 0.000 < 0.05 in the partial test (t-test). However, teacher professionalism did not have a significant moderating effect, as indicated by a significance value of 0.508 > 0.05 in the moderation test.Contribution- This study reinforces the theoretical framework that integrating augmented Reality with culturally relevant content (ethnomathematics) can effectively enhance teachers' competence in integrating technology, pedagogy, and subject matter